Evaluating the Effectiveness of Problem-Based Learning (PBL) in Schools: A Comprehensive Meta-Analysis - Deby Cinthia; Ganefri Ganefri; Asmar Yulastri; Giatman Giatman; Dedy Irfan; Hansi Effendi (STAI Hubbulwathan Duri, 2025)
Problem-Based Learning (PBL) has been widely promoted as a student-centered approach that fosters critical thinking. However, evidence from individual studies often varies across educational levels and contexts. This study aimed to synthesize empirical findings through a meta-analysis to evaluate the overall effectiveness of PBL in enhancing learners’ critical thinking skills. A systematic search was conducted across academic databases, yielding 2,250 articles. After applying inclusion and exclusion criteria, 25 studies were selected for analysis. Data were coded based on research design, educational level, and implementation characteristics. Statistical analyses were performed using both fixed-effect and random-effect models to estimate the pooled effect size. Publication bias was examined using Egger’s Test, Funnel Plot, and Rank Correlation Test. The meta-analysis indicated that PBL has a significant positive effect on critical thinking skills, with a pooled effect size of 1.134 (p 0.001) and a 95% confidence interval ranging from 0.730 to 1.537. A high heterogeneity level was observed (I² = 95.047%), suggesting variations in study characteristics such as instructional methods, learner populations, and cultural contexts. Although Egger’s Test suggested possible publication bias, Funnel Plot and Rank Correlation Test results supported the overall robustness of the findings. This study provides strong evidence that PBL is an effective strategy for improving critical thinking across different educational levels. Successful implementation requires adequate institutional support, teacher training, and contextual adaptation. The findings highlight the importance of adopting PBL more broadly as a framework for 21st-century education.